Martin Rantan-Farhan Political Communication In The Regional Head Election In Ketapang District, West Kalimantan Province 2020 - Antir, Antir; Elyta, Elyta; Saherimiko, Saherimiko (Cita konsultindo, 2024)
Political communication is a very important aspect in the political battle process to win council seats at both the central and regional levels. This research aims to describe and identify the political communication carried out by the winning regional head candidate pair Martin Rantan, SH, M.Sos, and Deputy Regional Head H. Farhan, SE, M.Si in Ketapang Regency in 2020. This research uses descriptive qualitative research. with analytical methods. Technique for determining informants using a natural setting. The data sources used are primary data sources and secondary data sources. The data collection technique for this research is by conducting interviews, observation, and documentation/library study. The results of the political communication research examined in this research on the Martin Rantan - Farhan pair as winners of the Regional Head election in Ketapang Regency, West Kalimantan Province in 2020 consist of; communicator, communication message, communication media, and audience. Based on interviews conducted by all sources related to political communication, it can be concluded that several parties were assigned as communicators in the case of the winning team, the Martin Rantan – Farhan pair, namely a successful team that was felt to have communicator abilities and performance as well as high credibility. The communication message of the couple Martin Rantan-Farhan is expressed in the form of socialization with the characteristic jargon, namely